Metrics for software conceptual models - Genero, Marcela, 1966-; Piattini, Mario, 1966-; Calero, Coral, 1968- (Imperial College Press, 2005)
The idea that "measuring quality is the key to developing high-qualitysoftware systems" is gaining relevance. Moreover, it is widelyrecognised that the key to obtaining better software systems is tomeasure the quality characteristics of early artefacts, produced atthe conceptual modelling phase